Contingency Analysis of Ethics Training in Psychology Programs in Colombia - Diana Paola Pulido-Castelblanco; Blanca Patricia Ballesteros-De Valderrama (MedUNAB, 2022)
ABSTRACT Introduction. The topic of ethics training in psychology has been constant in Colombia, especially since the Colombian Association of Psychology Faculties was created. However, reports of deficiencies in ethics training and research reviews, centered on identifying the ethical knowledge of students and professional actions in psychology, justify more complex studies. In this framework, relationships between contextual factors, which are necessary to understand the dynamics of psychological education, and factors related to ethically practicing the profession, must be included in the analysis. The objective of the study was, therefore, to demonstrate interdependent relations between the different actors that participate in ethics training, the interlocking of individual reinforcement contingencies and cultural consequences through a contingency analysis of psychology program curricula in Colombia. Methodology. A qualitative documentary análisis study with the methodology proposed by Todorov in terms of contingency analyses. Results. Interlocking practices were demonstrated in terms of metacontingencies in educational institutions, more focused on professional development than on ethics training. On an inter-institutional level, practices do not demonstrate a metacontingency in the strict sense, which was analyzed in light of the university autonomy and academic freedom policy. Malpractice can be considered a macrocontingency from the point of view of normalizing practices without an ethical reflection. Discussion. Psychological education is understood as a cultural practice that depends on relatively effectively interlocking contingencies, which prepares professionals who can adjust to the needs of society. This posture is coherent with the authors’ proposals. Conclusions. It is necessary to effectively integrate training in disciplinary skills with ethics, in order to attain a cultural practice in the terms of the analyzed metacontingency. RESUMEN Introducción. El tema de la formación ética en psicología ha sido una constante en Colombia, especialmente desde la constitución de la Asociación Colombiana de Facultades de Psicología. Sin embargo, los reportes de deficiencias en la formación ética y la revisión de investigaciones, centradas en identificar el conocimiento ético de los estudiantes y el actuar profesional en psicología, justifican un estudio más complejo. En este marco, las relaciones entre los factores contextuales, que son necesarios para comprender las dinámicas en la formación psicológica, y los factores relacionados con el ejercicio ético de la profesión deben incluirse en el análisis. El objetivo del estudio fue, entonces, evidenciar, a través de un análisis contingencial de los planes de estudio de los programas de psicología en Colombia, las relaciones de interdependencia entre los diferentes actores que intervienen en la formación ética, el entrelazamiento de las contingencias de refuerzo individual y las consecuencias culturales. Metodología. Estudio cualitativo de análisis documental con la metodología propuesta por Todorov en cuanto al análisis contingencial. Resultados. Se muestran prácticas entrelazadas en términos de metacontingencias en las instituciones formativas, más enfocadas al desarrollo profesional que a la formación ética. A nivel interinstitucional, las prácticas no evidencian una metacontingencia en sentido estricto, lo cual se analiza a la luz de la política de autonomía universitaria y de libertad de cátedra. La mala praxis puede considerarse como una macrocontingencia, desde el punto de vista de la normalización de prácticas sin una reflexión ética. Discusión. La formación en psicología se comprende como una práctica cultural, en función de contingencias entrelazadas de forma relativamente efectiva, que forma profesionales que se ajustan a las necesidades de la sociedad, postura que es coherente con lo propuesto por otros autores. Conclusiones. Es necesaria una integración efectiva del entrenamiento en competencias disciplinares con el de competencias éticas, con el fin de lograr una práctica cultural en los términos metacontingenciales analizados. RESUMO Introdução. A questão da formação ética em psicologia tem sido uma constante na Colômbia, especialmente desde a constituição da Associação Colombiana de Faculdades de Psicologia. No entanto, os relatos de deficiências na formação ética e a revisão de pesquisas, voltadas para identificar o conhecimento ético dos alunos e o comportamento profissional em psicologia, justificam um estudo mais complexo. Nesse quadro, as relações entre os fatores contextuais, necessários para compreender a dinâmica da formação psicológica, e os fatores relacionados ao exercício ético da profissão devem ser incluídos na análise. O objetivo do estudo foi, portanto, mostrar, através de uma análise contingencial dos planos de estudo dos programas de psicologia na Colômbia, as relações de interdependência entre os diferentes atores envolvidos na formação ética, o entrelaçamento das contingências de reforço individual e consequências culturais. Metodologia. Estudo qualitativo de análise documental com a metodologia proposta por Todorov em termos de análise de contingência. Resultados. Práticas entrelaçadas se mostram em termos de meta-contingências nas instituições formadoras, mais voltadas para o desenvolvimento profissional do que para a formação ética. No plano interinstitucional, as práticas não apresentam uma meta-contingência em sentido estrito, o que é analisado à luz da política de autonomia universitária e liberdade acadêmica. A práxis errada pode ser considerada uma macro-contingência, do ponto de vista da normalização de práticas sem reflexão ética. Discussão. A formação em psicologia é entendida como uma prática cultural, baseada em contingencias relativamente efetivamente entrelaçadas, que forma profissionais que se ajustam às necessidades da sociedade, posição condizente com a proposta por outros autores. Conclusões. É necessária uma integração efetiva da formação em competências disciplinares com a de competências éticas, a fim de alcançar uma prática cultural nos termos meta-contingenciais analisados.